Cobalt Doped Sulfonated Polyaniline with High Electrocatalytic Activity and Stability for Oxygen Evolution Reaction. Issue 43 (16th November 2022) - Vijayarangan, Murugan; Mathi, Selvam; Gayathri, Arunagiri; Jayabarathi, Jayaraman; Thanikachalam, Venugopal
Abstract: The oxygen (OER) evolution reaction plays a crucial role for storage of renewable energy sources but, active sites of the active electrocatalysis remain in challengeable. In this work, we have developed sulfonated polyaniline (SPANI) coordinated with Co sites to investigate the OER process. To improve the electrical conductivity and electrocatalytic efficiency towards OER herein, we report Co@SPANI synthesized by solvothermal method. The different physical characterization (SEM, TEM, XRD, IR, XPS and UV‐DRS) and electrochemical methods (voltammetry, chronopotentiometry and EIS) have been used to characterize Co@SPANI materials and examined the correlation of materials with activity. The cobalt doped SPANI (Co@SPANI‐800) exhibits higher electrocatalytic activity, showing smaller Tafel slope of 167 mV dec −1 with lower overpotential of 312 mV at 10 mA cm −2 in 1 M KOH, which reveal that abundant Co‐metal sites remarkably supporting the OER activity. Co@SPANI‐800 exhibits exceptional OER performances and durability over 200 h with loss of < 3.5 % in alkaline medium. At 1.54 V, solar powered water electrolysis confirmed the effectiveness of newborn electrocatalyst in solar energy to hydrogen energy conversion. Therefore, this work offered new path for designing materials as self‐supporting electrode for water splitting and for other potential applications. Abstract : The cobalt doped sulfonated polyaniline was synthesized by the solvothermal method at 120 °C. In the reason of the synergetic effect of cobalt‐doped sulfonated polyaniline elctrocatalyst (Co@SPANI‐800) provides nanocluster morphology, efficient electrocatalytic activity as well as ultra‐durability. That exhibits enhanced OER performance.